Pengaruh Penyuntikan Ekstrak Kelenjar Hipofisa Ayam Broiler Terhadap Pemijahan lkan Lele Dumbo (Clarias gariepinus Burchell) - Azhar Azhar; Masrizal Masrizal (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The objectives of this experiment was to study the effict of chicken hypophyse gland extract for spawning of cat fish. Each twenty four female and male cat fishes of about 1000-1050 g body weight/head were used in the experiments. Hypophyse gland extract were prepared from the hypophyse glands of broiler chickens. As treatments, the extract were injected in six different doses of 300. 400, 500, 600, 700 and 800 mg/kg body weight. Each doses was injected twice. The second injection were done after 4 hours. Each treatment consisted of 4 replications as block. Parameter measured included: spawning latent time, ovulation and egg maturation degree, water qualities (temperature, dissolved 02, free CO2, NH3 content and pH). Data were statistically analyzed by variance analysis in randomized block design (RBD). Results indicated that injection of broiler's hypophyse gland extract gave highly significant (P < 0.01) effect on the acceleration of spawning latent time (10 hrs). increase of percentage of ovulation (84.32%) and egg maturation degree (89,91 %). The optimal injection dose was found 741,95 mg broiler's hypophyse gland/kg catfish body weight.